FRI0496 Polyarteritis nodosa: over 20 years' clinical experience. (12th June 2018) - Sönmez, H.E.; Armağan, B.; Ayan, G.; Barut, K.; Batu, E.D.; Erden, A.; Uğurlu, S.; Bilginer, Y.; Kasapçopur, Ö.; Karadağ, Ö.; Bilgen, S.A.; Özdoğan, H.; et al.
Abstract : Background: Polyarteritis nodosa (PAN) is a necrotizing vasculitis of predominantly medium size vessels. Objectives: The present study aimed to summarise the characteristics of PAN patients, and also analyse the trend of decreasing PAN frequency in the last 25 years, in Turkey Methods: Paediatric and adult PAN patients followed up in Hacettepe University and Istanbul University Cerrahpasa Faculty of Medicine between 1990 and 2015, were included. The demographics, clinical findings and outcomes were evaluated retrospectively. Results: One hundred thirty-three patients, including 66 children, were enrolled in the study. The mean follow-up duration was 13 2–27 years. Among 133 patients, 86 (64.7%) had fever, 108 (81.2%) had skin involvement, 54 (40.6%) had renal involvement, 43 (32.3%) had neurological involvement, 32 (24.1%) had gastrointestinal involvement, 10 (7.5%) had cardiac involvement, 6 (4.5%) had pulmonary involvement. The median (minimum-maximum) leukocyte count, erythrocyte sedimentation rate and C-reactive protein levels at the time of diagnosis were 10400 (6100–32000)/mm 3, 58(2–132) mm/h and 5.22 (0–46) mg/dL, respectively. All patients were ANCA negative. Hepatitis serology was analysed in 121 patients and found positive in 13 of them. MEFV mutations were screened among 65 patients, 24 of them had mutations in at least one allele. Myalgia and skin involvement were significantly more frequent in children whereas neurologic involvement was much more common among adults (table 1). The number of PAN patients declined significantly after 2010 (figure 1). 9 patients were re-categorised as DADA2 after 2014 and no patient were diagnosed with FMF+. PAN after 2008 Conclusions: Our results suggest a decrease in PAN in our country which may be due to improved healthcare and dissecting mimicking diseases. Further prospective studies with prolonged follow-up could help us to better understand the disease characteristics. Reference: [1] Ozen S, et al. Childhood vasculitides in Turkey: a nationwide survey. Clin Rheumatol2007;26(2):196–200. Acknowledgements: None Disclosure of Interest: None declared